PROBLEMS OF FORMATION THE MONETARY POLICY IN THE RUSSIAN FEDERATION - E. Sakalo (Вестник университета)
The article is devoted to problems of the monetary policy in the Russian Federation. The article examines the goals established by the Central Bank before, and analyzed the degree of implementation at this stage.